Peningkatan Literasi Remaja Mengenai Regulasi dan Dampak Pernikahan Anak sebagai Langkah Menuju Generasi Emas Tahun 2024 di Desa Karang Sidemen, Kecamatan Batukeliang Utara, Lombok Tengah - Hilmi, Farida; Salsabila, Sally; Noviana, Mila (Jurnal Gema Ngabdi, 2025)
Child Marriage remains a critical challenge in Karang Sidemen Village, Batukeliang Utara district, Central Lombok Regency, undermining efforts to improve human resource development. Its persistently high prevalence is driven in part by limited public access to information on the consequences and legal frameworks governing child marriage. As a result, the practice continues, particularly among early adolescents who have dropped out of school or are still enrolled in junior or senior secondary education. This community outreach initiative aimed to strengthen public knowledge and awareness of the impacts and legal provisions related to child marriage. The program was implemented through three stages: preparation, implementation, and evaluation, with effectiveness measured using GU-PSPP, which demonstrates a positive and statistically significant improvement in participants' understanding of child marriage regulations and associated risks.